(untitled) (Research, Society and Development, 2021)
Botanical extracts with insecticidal properties seek to minimize the problems caused by the incorrect and often exaggerated use of pesticides. Depending on the concentration used and the extraction method, certain extracts can provoke different reactions on the harmful insects. Therefore, this study aimed to evaluate the toxicity of aqueous extracts prepared by maceration and infusion of Psychotria capillacea, Psychotria deflexa and Psychotria leiocarpa on eggs, larvae and pupae of Plutella xylostella. Seven treatments were used to evaluate the toxicity of the extracts: 1) P. capillacea infusion, 2) P. deflexa infusion, 3) P. leiocarpa infusion, 4) P. capillacea maceration, 5) P. deflexa maceration, 6) of P. leiocarpa maceration and 7) distilled water (control). Third-instar larvae of P. xylostella and pupae with up to three days of formation received topical application of the treatments, while fragments of cabbage containing eggs of this insect were immersed in the treatments. The results showed that the aqueous extracts by infusion and maceration of P. capillacea and P. leiocarpa and P. deflexa did not present significant toxicity on P. xylostella larvae and pupae, while the extracts prepared by maceration reduced the survival of eggs of this harmful insect. It was observed that macerated extracts caused mortality in the first 46 hours and infusions were more effective after this period. Therefore, other tests must be carried out to elucidate the efficiency of Psychotria extracts on the biological and behavioral parameters of P. xylostella, considering that new extraction techniques must be explored.